100 points!! ASAP!!
28th and 29th
spamming isn't allowed noobs.. aww XD
Attachments:
![](https://hi-static.z-dn.net/files/d75/4b57fe993a2155ab014d94e8281b90d6.jpg)
Answers
Answered by
5
Question :-
Therefore,
From equation (1) and (2) we get,
-ap + am + q -n = 0
a (m - p) = n - q [ Taking a common ]
*Refer the attachment for Second question Answer,
Step 1 = Let us consider p(x) as quadratic equation
Step 2 = The sums of roots α + β = - b/a
Step 3 = The product of roots αβ = = c/a
Over here,
a = a + 1
b = 2a + 3
c = 3a + 4
Attachments:
![](https://hi-static.z-dn.net/files/db4/d8abeceeaf07e406691b4ebed3602705.jpg)
Tomboyish44:
Awesome answer!
Answered by
2
Hope attachment can help you!
Attachments:
![](https://hi-static.z-dn.net/files/dd5/934daa385720e5ec4541c19090b67b5c.jpg)
Similar questions